2023
DOI: 10.3390/s23042322
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Individualized Sensory-Based mHealth Interventions to Improve Distress Coping in Healthcare Professionals: A Multi-Arm Parallel-Group Randomized Controlled Trial

Abstract: Detrimental effects of chronic stress on healthcare professionals have been well-established, but the implementation and evaluation of effective interventions aimed at improving distress coping remains inadequate. Individualized mHealth interventions incorporating sensor feedback have been proposed as a promising approach. This study aimed to investigate the impact of individualized, sensor-based mHealth interventions focusing on stress and physical activity on distress coping in healthcare professionals. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 105 publications
0
4
0
1
Order By: Relevance
“…Studies have demonstrated that biofeedback training alone targeting heart rate variability (HRV), a measure of autonomic nervous system activity, can lead to decreased stress levels and increased resilience to stressors [ 85 - 87 ]. Biofeedback interventions combined with diaphragmatic breathing, progressive muscle relaxation, and mindfulness meditation have also been used to alleviate stress [ 88 ]. 2) Anxiety disorders involve excessive and persistent worry, fear, and unease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have demonstrated that biofeedback training alone targeting heart rate variability (HRV), a measure of autonomic nervous system activity, can lead to decreased stress levels and increased resilience to stressors [ 85 - 87 ]. Biofeedback interventions combined with diaphragmatic breathing, progressive muscle relaxation, and mindfulness meditation have also been used to alleviate stress [ 88 ]. 2) Anxiety disorders involve excessive and persistent worry, fear, and unease.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, biofeedback training alone targeting skin conductance, a measure of sympathetic nervous system arousal, has been shown to reduce anxiety in individuals with generalized anxiety disorder [ 82 ]. Additionally, biofeedback techniques, such as heart rate variability biofeedback and electroencephalographic (EEG) biofeedback, have shown promise in alleviating symptoms of anxiety [ 55 , 88 ]. 3) Depression is a mood disorder characterized by persistent feelings of sadness, loss of interest, and impaired functioning.…”
Section: Discussionmentioning
confidence: 99%
“…The evidence for mHealth interventions being effective on physical activity is inconsistent [11], and these strategies do not consistently act as preventive measures against symptoms related to depression, anxiety, or stress-related indicators [12]. In the working population, we may have to consider the difference in the effectiveness of area-specific activities: occupational and transport activities are less positively associated with mental health than leisure-time activities pursued during free time [13].…”
Section: Challenges Of Promoting Physical Activity Among Workersmentioning
confidence: 99%
“…Abbildung 4 illus triert ein solches Design exemplarisch. (Chén & Roberts, 2021;Smith et al, 2018), wobei empirische Studien bislang heterogene Befunde hinsichtlich des zusätzlichen Nutzens individualisierter Interventionen lie fern (Baumann et al, 2023).…”
Section: Interventionen Zur Förderung Von Psychologischer Verbraucher...unclassified